Comparative Genomics of Emerging Lineages and Mobile Resistomes of Contemporary Broiler Strains of Salmonella Infantis and E. coli - Szmolka, Ama; Wami, Haleluya; Dobrindt, Ulrich (Frontiers in Microbiology, 2021)
Introduction. Commensal and pathogenic strains of MDR Escherichia coli and non-typhoid strains of Salmonella represent a growing foodborne threat from foods of poultry origin. MDR strains of S. Infantis and E. coli are frequently isolated from broiler chicks and the simultaneous presence of these two enteric bacterial species would potentially allow the exchange of mobile resistance determinants. Objectives. In order to understand possible genomic relations and to obtain a first insight into the potential interplay of resistance genes between enteric bacteria, we compared genomic diversity and mobile resistomes of S. Infantis and E. coli from broiler sources. Results. The cgMLST analysis of 56 S. Infantis and 90 E. coli contemporary strains revealed a high genomic heterogeneity of broiler E. coli. It also allowed the first insight into the genomic diversity of the MDR clone B2 of S. Infantis, which is endemic in Hungary. We also identified new MDR lineages for S. Infantis (ST7081 and ST7082) and for E. coli (ST8702 and ST10088). Comparative analysis of antibiotic resistance genes and plasmid types revealed a relatively narrow interface between the mobile resistomes of E. coli and S. Infantis. The mobile resistance genes tet(A), aadA1 and sul1 were identified at an overall high prevalence in both species. This gene association is characteristic to the plasmid pSI54/04 of the epidemic clone B2 of S. Infantis. Simultaneous presence of these genes and of IncI plasmids of the same subtype in cohabitant caecal strains of E. coli and S. Infantis suggests an important role of these plasmid families in a possible interplay of resistance genes between S. Infantis and E. coli in broilers. Conclusions. This is the first comparative genomic analysis of contemporary broiler strains of S. Infantis and E. coli. The diversity of mobile resistomes suggests that commensal E. coli could be potential reservoirs of resistance for S. Infantis, but so far only a few plasmid types and mobile resistance genes could be considered as potentially exchangeable between these two species. Among these, IncI1 plasmids could make the greatest contribution to the microevolution and genetic interaction between E. coli and S. Infantis.